2021
DOI: 10.18632/oncotarget.27890
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA hypermethylation pattern and unique gene expression signature in liver cancer from patients with Indigenous American ancestry

Abstract: Hepatocellular carcinoma (HCC) usually afflicts individuals in their maturity after a protracted liver disease. Contrasting with this pattern, the age structure of HCC in Andean people displays a bimodal distribution with half of the patients developing HCC in adolescence and early adulthood. To deepen our understanding of the molecular determinants of the disease in this population, we conducted an integrative analysis of gene expression and DNA methylation in HCC developed by 74 Peruvian patients, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 69 publications
0
18
0
2
Order By: Relevance
“…The identification of molecular signatures should eventually help to better sub-stratify these patients with no preoperative predictor and optimize medical intervention. 48,49 In conclusion, we believe that this new nomogram could represent a valuable tool to help decision-making of LR intervention or abstention in the management of HCC larger than 10 cm in diameter.…”
Section: Discussionmentioning
confidence: 85%
“…The identification of molecular signatures should eventually help to better sub-stratify these patients with no preoperative predictor and optimize medical intervention. 48,49 In conclusion, we believe that this new nomogram could represent a valuable tool to help decision-making of LR intervention or abstention in the management of HCC larger than 10 cm in diameter.…”
Section: Discussionmentioning
confidence: 85%
“…Proliferative HCC, characterised by high serum AFP levels, leads to more aggressive tumours and poor prognosis and is associated with HBV infection [62,65,67] . This unifying molecular classification aims to lead to stratified therapy strategies [68] . However, this classification has been based on studies carried out on HCC patients from Asia, Europe and North America, in which African and indigenous populations have been under-represented.…”
Section: Aetiology and Risk Factors For Hcc In Ssamentioning
confidence: 99%
“…First, Peruvian HCC displayed a unique mutation spectrum, in which the major class of alterations was epitomized by genetic short indels 6 . Second, the integrative analysis revealed that Peruvian tumors correspond to a divergent molecular subtype of HCC with unique gene expression signature and global DNA hypermethylation pattern, albeit genome-wide hypomethylation was hitherto viewed as a hallmark of HCC 7 . Third, liver parenchyma exhibited a very low level of inflammatory response and an absence of fibrotic process, and that, despite a strong prevalence of underlying infection with hepatitis B virus 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%